The Irony Of Intolerance Of Al-Qur'an Interpretation On Indonesian Social Media - Ida Kurnia Shofa; Feny Nida Fitriyani (The Pontianak State Institute of Islamic Studies, 2022)
Social media is one of the most influential things in human life. Its utilization is no longer for social interaction, more than that, it is used as a very effective shifting paradigm for the wider community. This article seeks to explore the irony of intolerance to the message of the Qur’an in Indonesian social media on one of the Da'wah Youtube channels. Using analytical descriptive method, this research is focused on da’wah YouTuber Firanda Andirja. The results of this study indicate that Firanda's da'wah youtube channel explores Islamic law in daily life and the interpretation of the verses of the Qur'an. In the interpretation of the Qur'anic verse, he does not use ta'wil, ta'thil and takyif so as to produce a rigid interpretation of other religious ideological group. The religious nuances that he adheres to make his interpretation cannot be purified from his ideology, so that it seems to defend a certain religious group is intolerant of other groups. Firanda's thought needs to be deconstructed, because the explanation of his interpretation contains rigid criticisms that are classified as being intolerant of the customs and culture of the Indonesian so that the explanation will actually cause new problems, especially since the interpretation was born in Indonesia which has multi-cultures and religions. So, the interpretation is not suitable when used as a moral-oriented interpretation reference.